EFFECTS OF DGAT1 AND GH1 POLYMORPHISM ON MILK YIELD IN HOLSTEIN COWS REARED IN TURKEY - Bilal Akyüz; Özgecan Korkmaz Ağaoğlu; Aytaç Akçay; Ali Reha Ağaoğlu (Slovenian Veterinary Research, 2015)
Summary: The aim of this study was to analyse the associations among the K232A polymorphism in the diacylglycerol acyltransferase1 (DGAT1) gene and L127V polymorphism in the bovine growth hormone (GH1) gene and milk yield in Holstein cows. A total of 281 first and second lactation Holstein cows from three different dairy cattle farms in the Burdur and Kayseri provinces of Turkey were included in this study. The PCR-RFLP method was used for DGAT1 and GH1 genotyping. The frequencies of genotypes and alleles of GH1 gene were found to be 0.78 for LL, 0.18 for LV and 0.04 for VV; 0.87 for the L allele and 0.13 for the V allele. The frequencies of genotypes and alleles of the DGAT1 gene were to be 0.61 for AA, 0.30 for KA and 0.09 for KK; 0.76 for the A allele and 0.24 for the K allele. No relations were found between DGAT1-K232A genotypes and the average milk yield in the first three lactations. However, an association between GH1-L127V polymorphism and the average milk yield of Holstein cows was found in the first three lactations. Cows with LL genotype had higher milk yield compared to LV and VV cows (P<0.05).